Random mutagenesis screening indicates the absence of a separate H+-sensor in the pH-sensitive Kir channels - Paynter, J; Shang, L; Bollepalli, M; Baukrowitz, T; Tucker, S (LANDES BIOSCIENCE, 2010)
Several inwardly-rectifying (Kir) potassium channels (Kin l 1, Kir41 and Kir4 2) are characterised by their sensitivity to inhibition by intracellular H+ within the physiological range The mechanism by which these channels are regulated by intracellular pH has been the subject of intense scrutiny for over a decade, yet the molecular identity of the titratable pH-sensor remains elusive In this study we have taken advantage of the acidic intracellular environment of S cerevisiae and used a K+-auxotrophic strain to screen for mutants of Kin 1 1 with impaired pH-sensitivity In addition to the previously identified K80M mutation, this unbiased screening approach identified a novel mutation (S172T) in the second transmembrane domain (TM2) that also produces a marked reduction in pH-sensitivity through destabilization of the closed-state However, despite this extensive mutagenic approach, no mutations could be identified which removed channel pH-sensitivity or which were likely to act as a separate H+-sensor unique to the pH-sensitive Kir channels In order to explain these results we propose a model in which the pH-sensing mechanism is part of an intrinsic gating mechanism common to all Kir channels not just the pH-sensitive Kin channels In this model mutations which disrupt this pH-sensor would result in an increase, not reduction, in pH-sensitivity This has major implications for any future studies of Kir channel pH-sensitivity and explains why formal identification of these pH-sensing residues still represents a major challenge